Impactos antrópicos na comunidade de macroinvertebrados bentônicos em lagos subtropicais - Alessio, Carlos Eduardo (2020)
In recent years, aquatic ecosystems have been the target of multiple environmental impacts resulting from man-made activities, which can be from domestic and industrial sources due to urbanization, but also huge amounts of pesticides and agricultural effluents, which can cause eutrophication of these environments. Thus, this study aims to compare urban and rural lakes of Toledo, PR based on water quality, sediment contamination and the macroinvertebrate community, in order to evaluate the toxicity of metals in sediments and water quality on the benthic community composition. For this purpose, 5 lakes were selected in the municipality, 3 in urban area and 2 in rural area. There were 4 samples, one per season of the year. Variables were measured to characterize water quality (Electrical conductivity, BOD, Total Phosphorus, Nitrate, Nitrite, Ammonia, Total Nitrogen, Dissolved Oxygen, pH, Water Temperature, Air Temperature, Transparency and Turbidity) and sediment (Total Phosphorus, Total organic carbon, organic matter, Cd, Pb, Cu, Cr, Mg, Mn and Zn). We estimate the sediments contamination factor for each metal, degree of contamination and potential ecological risk of each environment. Simultaneously, sediment samples were taken with a dredger for Macroinvertebrates community evaluation. Nine groups of Macroinvertebrates were found, being identified 03 Phylum, 04 classes and 08 families, registering 403 individuals. The water quality variables with the highest potential of explanation the macroinvertebrates community variation were Nitrate, Nitrite, Dissolved Oxygen, Total Phosphorus and Coliforms. The contamination factors more related to this community variation were Fe, Zn and Cd. Urban lakes presented a smaller number of individuals than rural lakes. The characteristics of water quality reflected more directly on the community as a function of land use and occupation. The characteristics of metal contamination factor in the sediment had a more subtle effect, but considerable. Therefore, we accept the proposed hypothesis that the macroinvertebrate community present in the lakes reflects seasonality, summarized by the variables of the water quality, as well as the degree of sediment contamination.